On the front line: integrated habitat mapping for olive ridley sea turtles in the southeast Atlantic. Issue 12 (31st July 2013) - Pikesley, Stephen K.; Maxwell, Sara M.; Pendoley, Kellie; Costa, Daniel P.; Coyne, Michael S.; Formia, Angela; Godley, Brendan J.; Klein, Warren; Makanga‐Bahouna, Junior; Maruca, Sheryl; Ngouessono, Solange; Parnell, Richard J.; et al.
Abstract: Aim: Knowledge and understanding of marine vertebrate spatial ecology are required to identify sources of threat and highlight areas for conservation. Olive ridley sea turtles Lepidochelys olivacea are in decline in some regions, and data for the Eastern Atlantic are sparse. Here, we seek to describe observed, and potential, post‐nesting habitats for this species in the southeast Atlantic. We contextualize these with fisheries catch data to identify areas of potential threat from fisheries interaction for this species. Location: West coast of Africa, southeast Atlantic. Methods: We tracked 21 female olive ridley turtles, from two nesting sites, between 2007 and 2010. We used ensemble ecological niche modelling, integrated with knowledge on the physical and biological oceanographic environment, to identify regions where environmental variables exist that may be critical in defining post‐nesting habitats for this species. We further integrate fisheries catch data to contextualize potential threat from fisheries. Results: We describe key areas of observed, and potential, olive ridley turtle occurrence at sea, and reveal that there was considerable overlap of these conspecifics, from two distinct nesting regions, within the Angolan exclusive economic zone (EEZ). With the inclusion of fisheries catch data for the region, we highlight areas that have the potential for conflict with fishing activities known to result in bycatch. Main conclusions: This study demonstrates that it is imperative that marine conservation policy recognizes the spatial extent of highly migratory species with expansive ranges. It also highlights that deficiencies exist in current knowledge of bycatch, both in gear specificity and in catch per unit effort. With integration of vessel monitoring system (VMS) data and those on fisheries catch, knowledge and understanding of bycatch may be improved, and this will ultimately facilitate development of appropriate management strategies and long‐term sustainability of fisheries and their supporting ecosystems.